2004
DOI: 10.1086/420820
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone-Resistant Haemophilus influenzae in a Long-Term Care Facility: Clinical and Molecular Epidemiology

Abstract: We describe a clonal outbreak of quinolone-resistant Haemophilus influenzae (QRHI) from an affiliated long-term care facility (LTCF-A); the outbreak was associated with the clinical use of levofloxacin, which was determined to be a risk factor for acquisition of QRHI. The minimum inhibitory concentration to which 90% of isolates were susceptible (MIC90), as determined by broth microdilution, was >4 microg/mL for levofloxacin, >2 microg/mL for moxifloxacin, >2 microg/mL for gatifloxacin, and 8 microg/mL for gem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
50
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 21 publications
0
50
1
1
Order By: Relevance
“…Recent reports have noted the prevalence of fluoroquinolone (FQ)-resistant H. influenzae (1,3,4,9,11,14,20,22,26). FQ-resistant H. influenzae often carries mutations in the quinolone resistance-determining regions (QRDRs) of the gyrA and the parC genes, which encode subunits of DNA gyrase and topoisomerase IV, respectively (9,11,16,18,23).…”
mentioning
confidence: 99%
“…Recent reports have noted the prevalence of fluoroquinolone (FQ)-resistant H. influenzae (1,3,4,9,11,14,20,22,26). FQ-resistant H. influenzae often carries mutations in the quinolone resistance-determining regions (QRDRs) of the gyrA and the parC genes, which encode subunits of DNA gyrase and topoisomerase IV, respectively (9,11,16,18,23).…”
mentioning
confidence: 99%
“…The recent increase in BLNAR strains has become a severe problem, leading to community-acquired infections (8,19). Fluoroquinolone-resistant H. influenzae isolates have occasionally been reported worldwide (1,4,13,15), but they have rarely been reported in Japan (9,10). Fluoroquinolones are effective against the causative agents of atypical pneumonia, such as Chlamydophila pneumoniae and Mycoplasma pneumoniae, as well as those of typical bacterial pneumonia, S. pneumoniae and H. influenzae.…”
mentioning
confidence: 99%
“…Concomitantly, the prevalence of resistant Streptococcus pneumoniae has increased (5,9), and occasionally resistant isolates of Haemophilus influenzae, which is generally highly susceptible to fluoroquinolones, have been recovered (1-4, 6, 10-12, 14, 15). Recently, an outbreak of levofloxacin-resistant H. influenzae was observed in a long-term care facility (13). Epidemiological data and electrophoretic analysis of DNA fragments from resistant isolates of the outbreak suggested that the resistant isolates were clonally related (13).…”
mentioning
confidence: 99%
“…Recently, an outbreak of levofloxacin-resistant H. influenzae was observed in a long-term care facility (13). Epidemiological data and electrophoretic analysis of DNA fragments from resistant isolates of the outbreak suggested that the resistant isolates were clonally related (13). To characterize the DNA regions likely to be responsible for the resistance, we have examined isolates for nucleotide sequence changes within mutational hot spots, called quinolone resistance-determining regions (QRDRs), of genes encoding DNA gyrase and DNA topoisomerase IV.…”
mentioning
confidence: 99%
See 1 more Smart Citation